Latihan Fisik terhadap Kadar Glukosa Darah dan Kualitas Hidup Penderita Diabetes Melitus Tipe 2 - Titanik, Geladis; Wahyudi, Andri Setiya; Pratiwi, Ika Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to evaluate the effect of physical exercise on blood glucose levels and quality of life in people with Type 2 Diabetes Mellitus. Methods This research uses a systematic review method referring to PRISMA guidelines. Research shows that physical exercise, especially a combination of aerobic and resistance, effectively improves quality of life and glycemic control in type 2 diabetes patients. High-intensity exercise can improve cardiorespiratory fitness. The combination of vitamin D supplementation and exercise training has a synergistic effect in enhancing insulin resistance. Concomitant aerobic and resistance exercise is recommended for managing type 2 diabetes, with HIIT being an effective intensity option. In conclusion, physical exercise, especially a combination of aerobic and resistance, effectively improves the quality of life and glycemic control in T2DM individuals. Keywords: Physical Activity, Type 2 Diabetes Mellitus, Glucose Levels